(untitled) (Mustansiria Dental Journal, 2004)
The purpose of the study to evaluate the periodontal status oral hygiene and gingival health) ni pregnant women and compare it with single females ni Mosul city. A total sample of (666) females (399 pregnant women and 267 single females) selected randomly, their age range was (18-39) years. The assessment of gingival health condition and oral hygiene was performed using gingival index by (Löe and Silness), plaque index by (Silness and Löe) and calculus index by (Bjorby and Löe). The study showed that there were high significant differences in mean of gingival, plaque and calculus indices between the pregnant and single females, except for the age group (18-24) years for calculus index. The results of study revealed no significant difference between age groups of pregnant women and for single females. Also the study demonstrated no significant difference between age groups of single females ni the mean plaque index, while there is an increase ni mean plaque score with the age for pregnant women. The study indicated that there was a significant increase ni mean calculus index with the age significantly, while the mean ni single females increase slightly with the age, and only the younger age group (18-24) years reported a lower significant mean than the older age groups (30-34 and 35-39) years.